The EFFECT OF TEACHER PERFORMANCE ON STUDENT LEARNING MOTIVATION IN DISTANCE LEARNING DURING COVID-19 PANDEMIC AT SMP NEGERI 20 BEKASI - Kiyat Yuliani; Nadia Rista (Jurnal Ilmu Pendidikan Ahlussunnah, 2021)
This study aims to reveal the effect of teacher performance (X) on student’s learning motivation (Y) in distance learning during the pandemic. The research method used is a quantitative method with data management using the SPSS 16.0 application. Analysis of the data used is simple regression analysis. The research sample is 53 students of SMP Negeri 20 Bekasi. The conclusion of the research revealed: (1) The significance test of the regression line equation was found that Fhit = 46,345 with a significance level of = 0,00 < 0,05 or Ho was rejected, then the regression model could be used to predict the participation variable. Thus, the Y or X regression is significant or the teacher’s performance has an effect on student’s learning motivation. (2) The significance test of correlation coefficient obtained the magnitude of the correlation coefficient, namely 0,690 and Fhit = 46,345 with p-value = 0,00 <0,05. This means that Ho is rejected, meaning that the correlation coefficients of X and Y are significant. While the percentage of the influence of the independent variable (teacher’s performance) on the dependent variable (student’s learning motivation) which is called the coefficient of determination is 0,476, which implies that the influence of teacher’s performance on student’s learning motivation is 47,6%.